JARINGAN SOSIAL ORGANISASI LESBIAN, BISEXUAL, DAN TRANSGENDER: STUDI KASUS ORGANISASI ARDHANARY INSTITUTE DI JAKARTA - Sri Setiawati (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2016)
This paper discusses the social networks that is done by Ardhanary Institute LBT Women (Lesbian, Bisexual, Transgender) organization in Jakarta. With the thesis that the environment in Indonesia are not permissive and cons with the presence of LGBT / LBT this organization even dare to "coming out", if it is not supported by an enabling environment through social networks. This discussion describes the social networks that made this organization, from building social relationships between actors / individuals up with foreign institutions (international) and domestic, as well as with the mass media.As the study of anthropology, then more emphasis on the social network that is descriptive, not at the level of analytics. Data collection technique was not  through measurement but more in the process of intensive observations, in-depth interviews and participatory observation. Using an ethnographic feminist approach, where the relationships globally can only be understood in the " real materials interlocked closely in the everyday encounter", namely action and everyday practicewhich became  the subject of ethnography research.Conclusions: 1). The social  network that is done  by Ardhanary Institute  organization through a relationship between actors and LBT/LGBT organizations in these areas. Externally also through multiple agencies (domestic and foreign). The actor, who is in this organization as a motivator, facilitator, and inspirator as well as the implications effect "struggling" for the movement of other LBT organizations in Indonesia 2). This organization is actively building a broader network through cooperation with other women's organizations, crisis centers, health care providers, safe houses, legal aid organizations and the National Commission for Women. And build working relationships with law enforcement agencies in providing assistance to victims of LBT violence.